2010
DOI: 10.1111/j.1365-2923.2010.03743.x
|View full text |Cite
|
Sign up to set email alerts
|

‘You’re judged all the time!’ Students’ views on professionalism: a multicentre study

Abstract: This research offers valuable insight into how Phase 1 medical students construct their personal and professional identities in both the offline and online environments. Acknowledging these learning mechanisms will enhance the development of a genuinely student-focused professionalism curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 40 publications
10
121
1
2
Order By: Relevance
“…While there is no clear, concise, and currently relevant description of professionalism, many residency programs have introduced the role-modeling methods and feedback from patients, attending physicians, nurses, and their peers [5][6][7]. Other programs have incorporated reflective practice to increase awareness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While there is no clear, concise, and currently relevant description of professionalism, many residency programs have introduced the role-modeling methods and feedback from patients, attending physicians, nurses, and their peers [5][6][7]. Other programs have incorporated reflective practice to increase awareness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…4 These tenets all can be undermined by the public online posting of comments or images that are contrary to these statements. Further complicating the matter, healthcare professions students struggle with the line between their professional identity and their personal identity 5 as is reflected by unprofessional postings seen on the profiles of professional students. In a study of medical student and resident Facebook accounts, Thompson and colleagues found that a small proportion of the students belonged to groups that had unprofessional names and had posted photos depicting drunkenness and/or overt sexuality, and/or used foul language in messages.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to avoid the need for re-examinations, everything should be done with as high quality as possible and under any conditions." (3rd year student) Interestingly, the radiography students of this study, unlike medics, 17 nurses 12 and other allied health professionals 7 did not refer to appearance, dress codes or self hygiene as a demonstration of and characteristic of professionalism.…”
Section: Professionalism and Unprofessionalismmentioning
confidence: 63%